Use of EB-CFRP to Improve Flexural Capacity of Unbonded Post-Tensioned Concrete Members Exposed to Partially Damaged Strands - Hayder Qays Abbas; Alaa Hussein Al‐Zuhairi (Salehan Institute of Higher Education, 2022)
The study presents the performance of flexural strengthening of concrete members exposed to partially unbonded prestressing with a particular emphasis on the amount (0, 14.2, and 28.5%) of cut strands-symmetrical and asymmetrical damage. In addition to examining the influence of cut strands on the remaining capacity of post-tensioned unbonded members and the effectiveness of carbon fiber reinforced polymer laminates restoration, The investigated results on rectangular members subjected to a four-point static bending load based on the composition of the laminate affected the stress of the CFRP, the failure mode, and flexural strength and deflection are covered in this study. The experimental results revealed that the usage of CFRP laminates has a considerable impact on strand strain. In addition to that, the flexural stiffness of strengthened members becomes increasingly significant within the serviceability phases as the damaged strand ratios increase. The EB-CFRP laminates increased the flexural capacity by approximately 13%, which corresponds to strand damage of 14.28% and about 9.5% for 28.57% of strand damage, which represents one of the unique findings in this field. Additionally, semi-empirical equations for forecasting the actual strain of unbonded tendons were presented. The suggested equations are simple to solve and produce precise results. Doi: 10.28991/CEJ-2022-08-06-014 Full Text: PDF